The Reflexive Classroom Manager: A Required Pre-Service Mode - T.G. Ryan (Networks: An Online Journal for Teacher Research, 2006)
In North America, interests that pervade postsecondary institutions are often covert, yet there is an identifiable pulse driving programs, research, conferences, and community service. The pulse can be identified as improvement, change, and innovation. We do this not because we are unwell, but rather as an ethical endeavor that infuses both mind and body in our search to advance our practices, society, and ourselves. Whether we are a student attending these large institutions or simply reflecting upon our current role as faculty we will be able to recall what our teachers did, or did not do, to help us in the past. If we could go back and talk to our teachers, we would identify what was done well and suggest what they might do to improve their teaching. Teacher improvement and training is something that touches all of us as it affects students, parents, professors, and the community at large.